2021
DOI: 10.18203/2320-6012.ijrms20212516
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of peak expiratory flow rate and single breath count in normal adults

Abstract: Background: Spirometry mandates the requirement of equipments and skilled technicians which may be difficult to acquire in resource limited situations. Thus simple alternative tests like Peak Expiratory Flow Rate (PEFR) and Single Breath Count (SBC) can be used to assess the pulmonary functioning of an individual.Methods: Hundred healthy participants of both genders between the age group of 18-50 years were recruited for this study. They were asked to perform PEFR using the Mini Wright Peak Flow Meter and SBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A total of 13 studies ( n =13) were included in the review out of which 10 studies were prospective studies 11 20 , 1 was retrospective 21 , 1 viewpoint 22 and 1 was cohort 23 altogether consisting of 1300 participants (sample size ranging from 22 to 516). Two studies 12 , 20 recruited healthy patients, and the remaining 10 studies recruited patients with one or more illnesses. The detailed characteristics of each study are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 studies ( n =13) were included in the review out of which 10 studies were prospective studies 11 20 , 1 was retrospective 21 , 1 viewpoint 22 and 1 was cohort 23 altogether consisting of 1300 participants (sample size ranging from 22 to 516). Two studies 12 , 20 recruited healthy patients, and the remaining 10 studies recruited patients with one or more illnesses. The detailed characteristics of each study are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Bhandare et al . 20 . in a study among 100 healthy participants with a mean age of 31.5 years found that SBC had a significant correlation of 0.7 with peak expiratory flow rate (PEFR).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates and analyzing titles and abstracts, of the 574 titles, 65 articles remained to be reviewed and analyzed in full, of which 24 were considered potentially relevant for this review. An indepth analysis defined the exclusion of 13 publications for not presenting results regarding the relationship between SBCT and VC in the scope [14,[27][28][29][30][31][32][33][34][35][36][37][38] (figure 1).…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…It varies with age, height, heath status of the person. 19 Surgeries like sternotomy for valve replacement reduce flow rate and the capacity to huff. In order to generate effective force while coughing to clear secretions from the airways.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SBC can be suitably used as a substitute for device-oriented measures, as it requires the use of no common device which could be a cause of risk of spread of infection amongst individuals. 19 Single breath count (SBC) is an economical and easily accessible parameter to assess the pulmonary functioning in an emergency setting where spirometry is not available. It is easy to perform and requires a simple tuning device (metronome).…”
Section: Introductionmentioning
confidence: 99%